(untitled) (Research, Society and Development, 2022)
The beer market, whether industrial or artisanal, is constantly growing in Brazil, making it the third largest beer producer in the world. Because of this, craft breweries are increasingly trying to adapt to quality control parameters, and bitterness measurement is one of them. The present study aims to evaluate whether the bitterness identified on the labels of beers, whether industrial or artisanal, of different styles, coincide with the value found through the validated analytical method of the European Brewery Convention. The methodology used consists of extracting the isomerization of α-acids, which is a hop resin, and the main responsible for giving the bitter taste of beer, so it is using the spectrophotometer by visible ultraviolet radiation, in which it measures, the presence of iso-α-acids present in beer, from the absorbance at a wavelength of 275nm, which is later converted to the Internatinal Bitterness Unit (IBU). The analyzed beers came from the state of Pernambuco and São Paulo, from artisanal and industrial production. The results obtained through the analyzes were within the specification range of their respective styles and their variation ranges from +1.56% to -7.55% in relation to what is identified by the manufacturers, with the smallest variation in industrial production and the greater in artisanal. The analyzed beers had a satisfactory result, in which the breweries that use the Glenn Tinseth method had values close to what is validated by the European Brewery Convention.